2007
DOI: 10.1002/ejoc.200700410
|View full text |Cite
|
Sign up to set email alerts
|

On the Structure of Cross‐Conjugated 2,3‐Diphenylbutadiene

Abstract: The structure of the cross-conjugated compound 2,3-diphenylbutadiene was investigated by single-crystal X-ray diffraction and computational methods. In the crystal structure the central butadiene fragment adopts an s-gauche geometry [-55.6(2)°torsion angle φ around the essential single bond], whereas the styrene moieties are close to planarity. MP2/6-311G* calculations show that the s-gauche conformation represents the global minimum along the φ coordinate, but also revealed the existence of an s-trans local m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Unsubstituted 2,3-diphenylbutadiene was previously found to adopt a somewhat surprising s-gauche conformation in the solid state, with a torsion angle of 55.61 around the butadiene single bond. 37,38 MP2 and DFT calculations supported that this compound possesses an s-gauche minimum, and also revealed the presence of an s-trans minimum, which is somewhat (depending on the calculation method up to 1.47 kcal mol À1 ) higher in energy. 38,39 The structures of DA1 and DA2 were investigated with 6-311G** DFT/B3LYP calculations.…”
Section: Molecular Structuresmentioning
confidence: 70%
See 1 more Smart Citation
“…Unsubstituted 2,3-diphenylbutadiene was previously found to adopt a somewhat surprising s-gauche conformation in the solid state, with a torsion angle of 55.61 around the butadiene single bond. 37,38 MP2 and DFT calculations supported that this compound possesses an s-gauche minimum, and also revealed the presence of an s-trans minimum, which is somewhat (depending on the calculation method up to 1.47 kcal mol À1 ) higher in energy. 38,39 The structures of DA1 and DA2 were investigated with 6-311G** DFT/B3LYP calculations.…”
Section: Molecular Structuresmentioning
confidence: 70%
“…37,38 MP2 and DFT calculations supported that this compound possesses an s-gauche minimum, and also revealed the presence of an s-trans minimum, which is somewhat (depending on the calculation method up to 1.47 kcal mol À1 ) higher in energy. 38,39 The structures of DA1 and DA2 were investigated with 6-311G** DFT/B3LYP calculations. In the optimized structure of DA1 (E = À481 363.76 kcal mol À1 ), the torsion angles between the double bond and the aniline and cyanophenyl groups amount to 36.91 and 41.31, respectively (Fig.…”
Section: Molecular Structuresmentioning
confidence: 70%
“…Interestingly enough, a similar torsion angle for this compound is found by electron diffraction in the gas phase [reference given by Roth et al (1991)], so that crystal packing effects can be excluded. In fact, quantum chemical calculations indicate that 2,3-diphenylbuta-1,3-diene also has the same conformation in the crystal and in the free molecule (van Walree et al, 2005). Thus, in both cases, the central torsion angle is a molecular rather than a crystal property.…”
Section: Figurementioning
confidence: 99%
“…X-ray diffraction, as reported by van Walree et al, of 2,3-diphenyl-1,3-diene shows s-gauche to be the preferred geometry with a face-to-face arrangement of the phenyl groups in the solid state. [13] The films of P1-P3 do consist mainly of the units in an s-gauche conformation. It has also been reported that multilayered chromophoric groups show large Stokes shift.…”
mentioning
confidence: 99%
“…P2 and P3 films also showed large Stokes shifts (see Figures S2 and S3 in the Supporting Information). [13] The films of P1-P3 do consist mainly of the units in an s-gauche conformation. X-ray diffraction, as reported by van Walree et al, of 2,3-diphenyl-1,3-diene shows s-gauche to be the preferred geometry with a face-to-face arrangement of the phenyl groups in the solid state.…”
mentioning
confidence: 99%